Wayang Purwa dan Tantangan Teknologi Media Baru - Riyanto, Bedjo (Institute of Research and Community Outreach - Petra Christian University, 2011)
The art of shadow puppets or wayang has been established as a Masterpiece of Oral and Intangible Heritage of Humanity by UNESCO. Leathermade shadow puppets or wayang kulit purwa as one of many wayang performances has been the most hegemonic, receiving much attention nationally as well as internationally until today. Therefore, there is an assumption that â€œthe realâ€ wayang is wayang kulit purwa. Globalization, commercialization, and the development of communication technology of popular culture influence greatly the advancement of wayang kulit purwa performances or even other wayang shows. Every stake holder of shadow puppet art truly needs the creative adaptive ability so that wayang can still be sustainable in the future.